Idiomatic expressions used by the Acehnese novelist Arafat Nur in the novel Tanah Surga Merah - Chairina Nasir; Azzah Ufairah (Universitas Syiah Kuala, 2023)
Writers as language users are fully aware that idioms are powerful tools to get messages across. This research is to examine idiomatic expressions in Arafat Nur’s novel Tanah Surga Merah (2017). It is intended to find out the types of idiomatic expressions and the contextual meaning used in the novel. The research design of this study was qualitative research. This study was aimed at finding out the seven types of idioms based on O’Dell and McCarty’s (2017) theory and Baker’s (2018) translation strategies for contextual meaning. The techniques of data analysis were data reduction, data display, and data verification suggested by Miles et al. (2018). After collecting and analysing the data from the novel, three types of idioms were found, with 30 idioms in total. There are eight idioms in the form of verb+object/complement/adverb or 27% of the share, 19 idioms in the form of compound, which is the most frequent type of idiom used with a percentage of 63%. Lastly, there were only three idioms in the form of simile, or 10% of the share. Idioms in the form of prepositional verbs, binomial (word+word), trinomial (word+word+word), and whole clauses or sentences were not found in this novel. In a nutshell, the contextual meaning of those idioms in the novel varied based on the situations and the contexts which function to describe feelings, emotions, and conditions in conversations. Paraphrasing is the most suitable translating strategy for equal meaning in English as it provides meaning in the context of the idioms found in the novel, and compound idioms are mostly used by the author to describe the characters in the novel.